2003
DOI: 10.1016/s1569-1993(03)00093-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in cystic fibrosis: the impact of gender, general health perceptions and disease severity

Abstract: Disease severity has an impact on HRQoL in adolescents and adults with CF. Some differences emerged between males and females, with females generally reporting poorer HRQoL. Evidence indicated that males and females perceived their health status differently, with females having a more accurate perception of objective clinical health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
6
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 25 publications
7
101
6
3
Order By: Relevance
“…9,10 However, the factors that contribute to health related quality of life (HRQOL) in patients with CF are unclear. A recent study that examined the impact of disease severity 11 on HRQOL found only modest relationships. The impact of anxiety and depression in relation to quality of life in CF patients is not fully known.…”
Section: Introductionmentioning
confidence: 96%
“…9,10 However, the factors that contribute to health related quality of life (HRQOL) in patients with CF are unclear. A recent study that examined the impact of disease severity 11 on HRQOL found only modest relationships. The impact of anxiety and depression in relation to quality of life in CF patients is not fully known.…”
Section: Introductionmentioning
confidence: 96%
“…In addition to cognitive therapy for body image disturbance, exercise is also a viable method for reducing negative body related self perceptions of body image disturbed individuals (Gee, Abbott, Conway, Etherington, & Webb, 2003). Previous studies have shown that exercise may alter body image for the better, not only in patients or disabled people, but also in healthy people (Rosen, Cado, Silber, Srebnik, & Wendt, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Disease severity showed an impact on HRQoL, together with gender in adults and adolescents (females had poorer HRQoL (6). Children were surveyed to assess the effect of newborn screening, which was not found associated with different HRQoL (7).…”
Section: Original Articlementioning
confidence: 99%